The Contributiion of Interactive Teaching Material in Pandemic ; Interctive Website and Automation - Andi Perdana Riyanto (STAI Nurul Islam Mojokerto, 2021)
Pandemic makes all the activity especially learningis to be done at home. The study contains the development of learning media college students using Edmodo. it is intended to prepare students to face the new era that called industrial era 4.0. it require students to master several application and auotomation.therefore, the instructor should be able to employ and use the aplication to enlighten the job. Its becomes the basis of this research to gain information wetheter storing the material and attendance list using Edmodo is helpful. The theory of R n D or called research and development is used. Some of the processes are storing the material, . This study shows that the content consequence is good and applicable. In addition, the reliability and practicality of the material in the Edmodo also show good results and acceptable